Expanding knowledge of Mexican Macrobiotus (Eutardigrada: Macrobiotidae): two new species from a bryophyte herbarium, with comments on national records - López-Sandoval, Daniel; Pérez, Tila M. (Zootaxa, 2026)
Herbaria are invaluable repositories for documenting past and present biodiversity and, beyond their botanical focus, provide historical snapshots of microhabitats that support diverse microfauna such as tardigrades. Bryophyte collections are particularly important in this regard, offering material for the discovery and characterisation of species. The genus Macrobiotus is taxonomically challenging due to high phenotypic variability, making species identification difficult and rendering several historical Mexican records doubtful under current integrative standards. In this study, we integratively describe two new species, Macrobiotus excelsus sp. nov. (within the hufelandi morphogroup), and Macrobiotus ignifer sp. nov. (within the persimilis morphogroup) and record Macrobiotus olgae for the first time in Mexico from moss samples from the Trans-Mexican Volcanic Belt housed in the National Herbarium of Mexico; M. excelsus sp. nov. represents the first documented tardigrade species from Veracruz. Morphological analyses using phase contrast microscopy and scanning electron microscopy, together with DNA sequencing, provided robust evidence for species delimitation. These findings represent a turning point in clarifying the taxonomy and phylogeny of Macrobiotus in Mexico and underscore the need to re-evaluate historical records using modern criteria. At the same time, they highlight the essential role of herbaria as key resources for discovering and characterising tardigrade diversity.